Identification of Suitable Ignition Conditions for Stable Switch from SI to HCCI of a Blowdown Supercharged Engine - Jagsch Michael; Yasuo Moriyoshi; Tatsuya Kuboyama (International Journal of Automotive Engineering, 2013)
In this paper, the necessary in-cylinder conditions for the transition from spark ignion (SI) to homogeneous charge compression ignition (HCCI) are analyzed. The hereby important factors for ignition time are investigated analytically. A control oriented combustion model, that is validated by experimental data, is used for sensivity analysis and a Monte-Carlo approach is taken to identify the important factors for transient HCCI and combustion mode switch. As a result, it was shown that the in-cylinder temperature plays a major role, exceeding other factors, such as the air-fuel ratio. The analytical conclusions are illustrated by numerical simulations after which the feasibility for actuation will be discussed. Final goal is to ensure a stable combustion in each cycle without crossing unstable combustion conditions.